Analogy, Transmutation, Resurrection: Three Framings of Octavio Paz’s Translation Practice - Washbourne, Kelly (2026)
Despite mounting research on his translation theoretics, Octavio Paz as a translator has been somewhat overlooked. Rather than a “unified field theory” of Pazian practice, Paz’s poetic output in English-to-Spanish translation, alone or in collaboration, and largely from his collected translations, Versiones y diversiones, will be mined to illustrate concretely the poet’s approach to translation. Paz is shown to see into a poem’s latency, but sometimes, artfully and indistinguishably, he interprets into digressionary translatio. Paz’s metaphorical figuration of translation as analogy, transmutation, resurrection frame analysis of his interventions in concrete textual cases.